2014
DOI: 10.1149/2.0191407jss
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Luminescence of CeAl11O18Based Phosphors by Replacement of (AlO)+by (SiN)+and Co-Doping with Eu

Abstract: A series of Si-N or Eu-Li doped CeAl 11 O 18 and CeAl 12 O 18 N phosphors are prepared by solid-state reaction. Their structure and luminescence are researched carefully. Si-N doping with the concentration less than 8% can be successfully dissolved into CeAl 11 O 18 crystal lattice and doesn't change the matrix structure, only resulting in crystal lattice shrinkage due to the shorter bond length for Si-N bond versus Al-O bond. It is observed that blue emission gradually decreases and UV emission becomes strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Namely, under 266 nm excitation these crystals show an intense complex luminescence band in the blue-yellow spectral range peaked at 476 nm (Fig.8b). Previously such luminescence under photoexcitation was also reported in СеAlO3 crystals [19]. It was suggested that not the host, but the admixture CeAl11O18 phase is responsible for this emission.…”
Section: Optical Propertiesmentioning
confidence: 58%
“…Namely, under 266 nm excitation these crystals show an intense complex luminescence band in the blue-yellow spectral range peaked at 476 nm (Fig.8b). Previously such luminescence under photoexcitation was also reported in СеAlO3 crystals [19]. It was suggested that not the host, but the admixture CeAl11O18 phase is responsible for this emission.…”
Section: Optical Propertiesmentioning
confidence: 58%
“…In sample STD1200, neither a CeAlO 3 nor a CeAl 11 O 18 phase was detected, but with increasing temperature, CeAlO 3 was identified in small amounts at 1250 °C. The CeAl 11 O 18 phase only appeared in the composition at high sintering temperatures (1300 °C), proving that it forms at high temperatures [ 52 ]. For the asymmetric graphite configuration, the CeAl 11 O 18 phase appeared in all the samples, and its amount increased with sintering temperature shown by the increasing intensity of its diffraction peaks.…”
Section: Resultsmentioning
confidence: 99%
“…However, the luminescence intensity of Al 10 O 3 N 8 :Eu 2+ phosphor still cannot be comparable with commercial BAM:Eu 2+ phosphor. Inspired by the doping favoring improved luminescence [28,29], the effect of Si-N substitution for Al-O bond on the luminescence is investigated preliminarily. Amazingly, the luminescence intensity is notably increased after Si-N doping.…”
Section: Resultsmentioning
confidence: 99%